Distribution of toxic chemicals in particles of various sizes from mainstream cigarette smoke. (28th January 2016) - Wang, Hongbo; Li, Xiang; Guo, Junwei; Peng, Bin; Cui, Huapeng; Liu, Kejian; Wang, Sheng; Qin, Yaqiong; Sun, Peijian; Zhao, Le; Xie, Fuwei; Liu, Huimin
Abstract: To accurately estimate the risk of inhaling cigarette smoke containing toxic chemicals, it is important that the distribution of these chemicals is accurately measured in cigarette smoke aerosol particles of various sizes. In this study, a single-channel smoking machine was directly coupled to an electrical low-pressure impactor. The particles of mainstream cigarette smoke were collected using 12 polyester films, and the particulate matter (PM) was characterized. Nicotine, tobacco-specific N-nitrosamines (TSNAs, including NNN, NAT, NAB, and NNK), polycyclic aromatic hydrocarbons (PAHs, including benzo(a)pyrene (BaP), benzo(a)anthracene, and chrysene), and heavy metals (including Cr, As, Cd, and Pb) present in the particles of different sizes were analyzed by GC, HPLC-MS/MS, GC/MS, or ICP-MS, respectively. The results demonstrated that the nicotine, TSNAs, PAHs, and heavy metals in mainstream cigarette smoke were dispersed over a particle size ranging from 0.1 μm to 2.0 μm, and the concentration of these toxic chemicals initially increased and then decreased the particle size grew. The distribution of nicotine was uniform for the PM in the size ranges of less than 0.1 μm, 0.1–1.0 μm, and 1.0–2.0 μm, TSNAs and heavy metals in particles of less 0.1 μm were more abundant, and PAHs in fine particles were also more abundant.